Flexible Configuration of Wireless Sensor Network for Monitoring of Rainfall-Induced Landslide - Quoc-Anh Gian; Duc-Tan Tran; Dinh-Chinh Nguyen; Tien Dieu Bui (Institute of Advanced Engineering and Science, 2018)
Establishment of wireless sensor network for Monitoring and Early Warning System (MEWS) of rainfall-induced landslide is still a challenging task due to problems of energy consumption. This research aim is to propose a new flexible system for the configuration of MEWS for rainfall-induced landslides. The proposed system is an integration a star topology and a tree topology, in which, the star topology is automatically used for the sensor nodes around the gateway node, whereas the tree topology is adopted for the other nodes. Consequently, the proposed configuration method is flexible and capable to save the energy consumption in the MEWS. Experiment result showed that the performance of the MEWS with the proposed method Wireless Sensor Network is better than those from the systems only use the tree topology or the star topology. The result of this study is useful for designing WSN for MEWS of rainfall-induced landslides.